Cost Sharing in Medicaid: Assumptions, Evidence, and Future Directions. (August 2016) - Powell, Victoria; Saloner, Brendan; Sabik, Lindsay M.
Several states have received waivers to expand Medicaid to poor adults under the Affordable Care Act using more cost sharing than the program traditionally allows. We synthesize literature on the effects of cost sharing, focusing on studies of low-income U.S. populations from 1995 to 2014. Literature suggests that cost sharing has a deterrent effect on initiation of treatments, and can reduce utilization of ongoing treatments. Furthermore, cost sharing may be difficult for low-income populations to understand, patients often lack sufficient information to choose medical treatment, and cost sharing may be difficult to balance within the budgets of poor adults. Gaps in the literature include evidence of long-term effects of cost sharing on health and financial well-being, evidence related to effectiveness of cost sharing combined with patient education, and evidence related to targeted programs that use financial incentives for wellness. Literature underscores the need for evaluation of the effects of cost sharing on health status and spending, particularly among the poorest adults.